Elastic measurements in ultra-thin polymer structures - Farmer, David John (2016)
This thesis contains details of a series of experiments performed to investigate the acoustic and elastic properties of ultra-thin polymer structures. Three main investigations were conducted. The first involved studying quantised vibrations in ultra-thin (∼100 nm) polystyrene films on silicon substrates. These films were vibrated via the picosecond acoustic technique, an optical pump-probe method. Quantised, harmonic vibrations were observed in the films with frequencies of the order of 10 GHz. The polymer films were then loaded by evaporating small thicknesses (2.5 - 30 nm) of gold. The frequencies of loaded areas were observed relative to the unloaded films. This frequency shift is described via a theory that considers the elastic wave equation in the structure with appropriate boundary conditions. Excellent agreement between experiment and theory is achieved, suggesting the potential for using these films as ultra-sensitive mass sensors. The second experimental chapter deals with experiments performed on polymer Bragg reflectors. These multilayer structures were again investigated via the picosecond technique. The reflected intensity of the probe laser beam was observed to be modulated by the strain pulse as it travelled through the structure. These results were compared to theoretically generated signals and this comparison suggests that, in the polymer structures considered here, the modulation can be described almost exclusively by the photo-elastic effect. Although the modulation is small it opens up the possibility of using similar structures in combinations with micro-cavities to act as high frequency optical components. The final experimental chapter details attempts to develop a new metrology for elastic properties in ultra-thin polymer films floated on a water surface. The films were cut into annuli and placed on a Langmuir-Blodgett trough before surfactant was placed around the outside. By moving the barriers of the trough, a surface pressure difference between the inside and outside of the annulus could be controlled and a wrinkling pattern induced around the annulus. A system for imaging and counting the wrinkles as a function of the surface pressure difference was developed and a theory that attempts to describe this is detailed. While the experimental technique is successful in producing highly controlled, reproducible wrinkles, the theoretical analysis currently overestimates the Young's modulus of the films. The reasons for this as well as avenues for further work are considered. The results of these three investigations all demonstrate the rich physics accessible in ultra-thin polymer films. Furthermore, it points to their potential to b e a key material as devices are more commonly manufactured at the nano-scale.